Responsibilities and legal consequences of land deed drafting officials (PPAT) for deeds they make that give rise to double certificates - Aslan Noor; Muhammad Yusuf; Kusmiadi, Kusmiadi; Karin Veronica Wijaya; Ilva Yuniarsi Maruf (Jurnal Info Sains : Informatika dan Sains, 2024)
Multiple certificates in land transactions can have serious legal consequences, such as ownership disputes, legal uncertainty, and financial losses for the parties involved. This research aims to explore and analyze the responsibilities and legal consequences faced by Land Deed Making Officials (PPAT) in the context of making land deeds which result in the issuance of multiple certificates. This research uses a normative legal approach. The results of this research highlight the central role of Land Deed Officials (PPAT) in the context of land buying and selling transactions and their impact on the possibility of creating multiple certificates. Research shows that non-compliance with material requirements and falsification of data by one of the parties, such as a seller who does not have rights to the land he is selling, can result in the land sale and purchase deed being invalid. As a consequence, land certificates issued based on the invalid deed also become invalid and can be cancelled. Regarding legal responsibility, PPATs who are proven guilty may face criminal and administrative sanctions, including prison sentences, fines, as well as reprimands or dismissal from their positions. A better understanding of regulations and effective monitoring of PPAT performance is the key to maintaining the integrity and trust of the public in the land system. Thus, this research contributes to deepening understanding of the dynamics of the relationship between PPAT, land transactions and related legal aspects.